UK offshore, maintaining self-sufficiency proceedings of the Conference on UK Offshore, Maintaining Self-Sufficiency, organized by the Institution of Civil Engineers and held in London on 9-10 October 1985. (Thomas Telford, 1986)
Focusing on the UK offshore industry, these papers discuss prospects and demands, look at the economics and government environment, provide case studies and changes for the future, and highlight new developments.
Keywords: Offshore oil well drilling -- Congresses.; Natural gas in submerged lands -- Great Britain -- Congresses.; elektronické knihy; electronic books